2019
DOI: 10.1371/journal.pone.0224245
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical, histological and computed tomography comparisons of the eye and adnexa of crab-eating fox (Cerdocyon thous) to domestic dogs

Abstract: An understanding of species' morphological and physiological parameters is crucial to developing conservation strategies for wild animals kept in human care. Detailed information is lacking for crab-eating fox (Cerdocyon thous) eyes and adnexa. Therefore, the aim of this study was to describe anatomical, histological and computed tomography (CT) features of the eye and adnexa in crab-eating fox, compared to domestic dogs. CT of the eye and adnexa of one live animal and a frozen specimen was performed for anato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(47 citation statements)
references
References 37 publications
5
24
0
Order By: Relevance
“…Therefore, infection may spread from these cavities to the orbital structures (Singh, 2018). In agreement to our results, the orbital rim of the crab‐eating fox is incomplete dorsolaterally (Lantyer‐Araujo et al., 2019). Consequently, the orbit is accessible for surgery without bone resection (Singh, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, infection may spread from these cavities to the orbital structures (Singh, 2018). In agreement to our results, the orbital rim of the crab‐eating fox is incomplete dorsolaterally (Lantyer‐Araujo et al., 2019). Consequently, the orbit is accessible for surgery without bone resection (Singh, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…The obtained results of the eyeball macroscopic measurements performed in the examined Asiatic black bear were similar to the brown bear, American black bear Ursus americanus , grizzly bear Ursus arctos horribilis and sloth bear Melursus ursinus [ 26 , 66 ], but also they were similar to the measurements made on some representatives of the Canidae family (crab-eating fox Cerdocyon thous , Arctic fox Alopex lagopus and bush dog Speothos venaticus ) compared to mongrel dogs, South African painted dog Lycaon pictus , wolves Canis lupus , gray fox Urocyon cinereoargenteus and red fox Vulpes , where the eyeball measurements were characterized by much higher parameters [ 25 , 66 , 67 , 68 ]. However, some species of Mustelidae and the only representative of Ailuridae red panda Ailurus fulgens [ 25 , 66 , 69 ] are characterized by small and medium dimensions of the eyeball compared to Ursidae and Canidae.…”
Section: Discussionsupporting
confidence: 67%
“…In the examined terrestrial caniforms, the pupil was characterized by different shapes and for example, the pupil in our examined Asiatic black bear was big and round in shape, similar to that of other bear species subfamily Tremarctinae and Ursinae and also in the domestic dog and in some wild Canidae ( Chrysocyon brachyurus , Canis lupus , Lycaon pictus pictus ) [ 68 , 96 ], and according to Kirbas Dogan et al, 2020 [ 26 ], the brown bear Ursus arctos horribilis the pupil had a wider temporonasal length, while vertically slit-shaped in the giant panda, Cerdocyon thous and Vulpes [ 3 , 67 , 86 , 96 , 97 ] and in North American racoon Procyon lotor as nocturnal animals the pupil is wide [ 98 ]. Johnson, 1901 [ 24 ] reported that the pupil in Ursidae is round except Ursus americanus , in which it is vertically oval, dilatating to a full circle.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations